Simultaneous EUS-FNA Diagnosis and TNM Staging of a Pancreatic Neuroendocrine Tumor in a Patient with an Unrecognized MEN Type 1 - Francesco Ferrara; Carmelo Luigiano; Antonella Maimone; Marco Bassi; Anna Maria Polifemo; Paola Baccarini; Vincenzo Cennamo; Nadia Cremonini; Carlo Fabbri (Case Reports in Oncological Medicine)
We report the case of a woman who, during oncological followup for bronchial carcinoid (diagnosed in 2005), papillary thyroid carcinoma, and bilateral parathyroid adenoma (simultaneously diagnosed in 2007), performed a pancreatic endoscopic ultrasonography with fine needle agobiopsy (EUS-FNA) for a positron emission tomography (PET) suspicion of pancreatic and hepatic lesions; during the procedure, the pancreatic and liver lesions were confirmed, and a peripancreatic lymph node involvement was found, allowing a complete pTNM staging during the same procedure.